Perancangan Produk dan Penjualan Multikategori melalui Platform E- Commerce Berbasis OpenCart di Kec. Padang Gelugur - Fadil, Ilham; Annas, Firdaus; Hidayat, Rahmad (JOVISHE : Journal of Visionary Sharia Economy, 2024)
This research aims to enhance the promotional power of MSME products and introduce the quality and uniqueness of products produced by MSMEs in the Padang Gelugur District, so that they can reach a wider market. The type of research used is qualitative, with the main methods being observation and interviews. Based on the observation results, several key challenges faced by MSME actors were identified, one of which is the still traditional sales techniques. Product sales are typically conducted only within the Padang Gelugur District, without expanding to areas outside the region. This poses a challenge, especially given the current technological advancements that have opened up new opportunities for product marketing. Many business owners are now utilizing digital platforms such as WhatsApp, Instagram, and online marketplaces like Shopee to promote their products. This research employs a Research and Development (R&D) approach with the PPE (Planning, Production, Evaluation) development model. This model is expected to enhance the effectiveness of promotional strategies while also encouraging the development of MSME products in the Padang Gelugur District. By utilizing digital technology, MSME actors can more easily reach consumers outside the region, increase competitiveness, and strengthen the sustainability of their businesses amid an increasingly competitive market. businesses in the midst of increasingly competitive market competition.